Van Nellefabriek Rotterdam : world heritage of a world port - Kuipers, Marieke C., 1951- (Rotterdam : nai010 Publishers, 2017)
"The iconic Van Nelle factory is inextricably linked to the dynamic world port of Rotterdam. This modernist masterpiece along the Schie was originally built for the processing and packaging of coffee, tea and tobacco. The neon sign on the roof testifies to this history. After careful re-use, the Van Nelle factory is now in use for the creative industry and as an event location. Meanwhile, this grand 'poem in steel and glass' is on the Unesco World Heritage List and is partly accessible to the public. This handy guide gives a clear explanation of the special features of the Van Nelle factory"--Page [4] of cover
Includes bibliographical references
Keywords: Van Nellefabriek (Rotterdam, Netherlands) -- Guidebooks; Architecture -- Guidebooks -- Netherlands -- Rotterdam; Rotterdam (Netherlands) -- Guidebooks -- Buildings, structures, etc; Rotterdam (Netherlands) -- Guidebooks -- History